The African Continental Free Trade Area and Foreign Direct Investment in West Africa: A Panel Data Analysis - Bajah, Jeff T. (International Journal of Economics and Financial Issues, 2026)
This study examines the impact of the African Continental Free Trade Area (AfCFTA) on foreign direct investment (FDI) inflows to West African countries. Using a difference-in-differences approach with panel data from 25 African countries over the period 2015 to 2024, we compare FDI trends in 15 ECOWAS member states (treatment group) with 10 Central African countries (control group) before and after AfCFTA's operational launch in January 2021. Our fixed effects regression analysis reveals a positive association between AfCFTA implementation and FDI inflows, with ECOWAS countries experiencing approximately 2.4 percentage points higher FDI (as a share of GDP) relative to the control group in the post-implementation period. While this effect approaches statistical significance at the 10% level, the results suggest economically meaningful potential benefits of regional trade integration for attracting foreign investment. Inflation emerges as a significant determinant of FDI, with higher inflation rates negatively associated with investment inflows. These findings contribute to the emerging literature on AfCFTA's economic effects and provide policy-relevant insights for West African governments seeking to leverage regional integration for investment promotion.